Pulmonary metastasis of stage I, low-grade endometrioid carcinoma: two case reports and the literature review - Wang, Li; Li, Yingxue; Han, Lin (Frontiers in Oncology, 2023)
Endometrial cancer (EC) is the most common malignant tumor of the female reproductive system and the majority of EC are low histological grade and confined to the uterus, resulting in a good prognosis. However, metastasis to the lung from a low-grade and early-stage endometrial endometrioid carcinoma (ECC) is extremely rare. Therefore, it is crucial to accurately differentiate between primary pulmonary malignancy and extra-thoracic malignancy presenting as metastatic disease, and flexible bronchoscopy with tissue acquisition plays a key role in this process. Despite its importance, there is limited literature available on the cytology of metastatic endometrial carcinoma in liquid-based cytology of bronchial brush (BB). In this article, we present two rare cases of lung metastasis from low-grade and early-stage endometrial endometrioid carcinoma, along with a detailed analysis of the cytologic features observed in BB samples. These cases highlight the significance of cytological and histological pathology, complemented by immunohistochemistry (ICH) analysis, in the diagnosis and management of ECC patients. Pathologists should pay close attention to these aspects, while gynecologists need to be mindful of the follow-up and management of early-stage, low-grade ECC patients. By focusing on these areas, healthcare professionals can effectively contribute to the improved care and outcomes of patients with ECC.